2001
DOI: 10.1523/jneurosci.21-07-02256.2001
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Distinct Signal Pathways, Including an Autocrine Neurotrophic Mechanism, Contribute to the Survival-Promoting Effect of Depolarization on Spiral Ganglion NeuronsIn Vitro

Abstract: We have shown previously that BDNF, neurotrophin-3 (NT-3), chlorphenylthio-cAMP (cpt-cAMP) (a permeant cAMP analog), and membrane depolarization promote spiral ganglion neuron (SGN) survival in vitro in an additive manner, depolarization having the greatest efficacy. Expression of both BDNF and of NT-3 is detectable in cultured SGNs after plating in either depolarizing or nondepolarizing medium. These neurotrophins promote survival by an autocrine mechanism; TrkB-IgG or TrkC-IgG, which block neurotrophin bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 105 publications
(196 reference statements)
7
119
1
Order By: Relevance
“…Because NT-3 has been shown to promote survival of spiral ganglion neurons in vivo and in vitro (Avila et al, 1993;Mou et al, 1997;Hansen et al, 2001;Fritzsch et al, 2004), one mechanism could be that NT-3 selectively promotes the survival of a subpopulation of spiral ganglion neurons. Our laboratory has shown previously that putative type II spiral ganglion neurons differ in the base from their type I counterparts by demonstrating slow accommodation, longer latencies, and prolonged membrane time constants (Reid et al, 2004), similar to neurons exposed to the appropriate concentrations of NT-3 in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Because NT-3 has been shown to promote survival of spiral ganglion neurons in vivo and in vitro (Avila et al, 1993;Mou et al, 1997;Hansen et al, 2001;Fritzsch et al, 2004), one mechanism could be that NT-3 selectively promotes the survival of a subpopulation of spiral ganglion neurons. Our laboratory has shown previously that putative type II spiral ganglion neurons differ in the base from their type I counterparts by demonstrating slow accommodation, longer latencies, and prolonged membrane time constants (Reid et al, 2004), similar to neurons exposed to the appropriate concentrations of NT-3 in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that electrical stimulation, such as the stimulation by cochlear implants, can lead to increased survival of SGCs after loss of hair cells; however, the effects of electrical stimulation alone were found to be less than the clinically acceptable level of survival for SGCs -even when stimulation was initiated immediately after deafening. 31,32 Some studies further indicate that electrical stimulation may attenuate the rapid degeneration of spiral ganglion neurons that follows withdrawal of neurotrophin therapy. For example, Maruyama et al demonstrated that SGCs survival was preserved after termination of intracochlear infusion with a glial cell line-derived neurotrophic factor in combination with the use of an electrical stimulation from a cochlear implant.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic AMP elicits a wide range of cellular functions; it is reported to be involved in neuronal survival, axonal regeneration, and enhancement of neurite outgrowth (Hansen et al, 2001;Kao et al, 2002;Rydel and Greene, 1988). Activation of the EP3 receptor has been shown to inhibit cAMP synthesis in murine platelets (Fabre et al, 2001).…”
Section: Discussionmentioning
confidence: 99%